Historical-Romanistic Study of the Institution of the Ombudsman - Carmen Jimenez Salcedo (Journal of Interdisciplinary History of Ideas)
Interest in the Ombudsman has recently increased, prompting the legal debate on the possibility that this institution with a strong democratic profile be granted certain flexible jurisdictional powers, accessible procedures and the creative development of regulatory standards at national and supranational level. In particular, at the level of the European Union (EU), some studies have shown an improvement in the behavior and responsibility of EU institutions and bodies as a result of an intervention that seeks to incorporate good administrative standards and their control. In this sense, and as Romanists, it is our duty to highlight the true origin of the institution in the defensor civitatis and, through its study, to provide keys to help build a more effective legislative framework that takes into account elements and parameters of utility that Roman Law has provided to the international legal experience throughout history and will continue to provide in the future.